Fertility Decline in Rwanda: Is Gender Preference in the Way?. (6th June 2013) - Habimana Kabano, Ignace; Broekhuis, Annelet; Hooimeijer, Pieter
Abstract : In 2007 Rwanda launched a campaign to promote 3 children families and a program of community based health services to improve reproductive health. This paper argues that mixed gender offspring is still an important insurance for old age in Rwanda and that to arrive at the desired gender composition women might have to progress beyond parity 3. The analyses are twofold. The first is the parity progression desire given the gender of living children. The second is gender specific replacement intention following the loss of the last or only son or daughter. Using the Demographic and Health Surveys of 2000, 2005, and 2010, we show that child mortality does not lead to extra parity progression beyond three, while having single gender offspring does and even more so when this is the result of the loss of the last son or daughter.